The Influence of Customer Relationship Management and Hospital Image on Outpatient Satisfaction at H. Padjonga Daeng Ngalle Regional General Hospital, Takalar Regency (International Forum of Researchers and Lecturers, 2025)
Background: Patient satisfaction is one of the important variables that must be considered in healthcare services when comparing expectations with the care received from hospital organizations. In the last three years, patient satisfaction data at H. Padjonga Daeng Ngalle Regional General Hospital, Takalar Regency has fluctuated. In 2021, the percentage of outpatient satisfaction reached 85%, in 2022 it increased to 92%, and in 2023 it decreased to 83%. Objective: The purpose of this study is to determine the effect of CRM and hospital image on outpatient satisfaction at H. Padjonga Daeng Ngalle Regional General Hospital, Takalar. Research Method: The research uses a quantitative approach with a cross-sectional study design. The sample consists of 398 respondents, all of whom are outpatients. A simple random sampling technique was employed. The study utilizes chi-square tests and regression analysis using SPSS software. Results and Conclusion: The results indicate that there is an effect of CRM (p=0.000) and hospital image (p=0.000) on patient satisfaction. Additionally, the F-test result shows (p=0.000), which allows us to conclude that there is a simultaneous effect of CRM and hospital image on outpatient satisfaction at H. Padjonga Daeng Ngalle Regional General Hospital, Takalar. Suggestions: The hospital should be able to maintain good relationships (CRM) with patients, for example, by communicating effectively when explaining the patient's diagnosis. The goal is to ensure that patients understand the information provided. This, in turn, will affect patient satisfaction.